2019
DOI: 10.1021/acsinfecdis.9b00355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Structural Study of Terminal Ends of Lipoarabinomannan from Mice Infected Lung Tissues and Urine of a Tuberculosis Positive Patient

Abstract: Mycobacterium tuberculosis lipoarabinomannan (LAM) is a biomarker for active TB disease. The presence of LAM in urine of TB patients, whether HIV positive or negative has been validated by a gas chromatography/mass spectral method with good specificity (84%) and sensitivity (99%). However, point-of-care (POC) methods to detect TB LAM in urine using immunoassays have poor sensitivity and are limited to only HIV co-infected TB diagnosis. We hypothesized that these disappointing results with the POC methods may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 53 publications
0
47
1
Order By: Relevance
“…According to the capping motifs, LAM can be classified into three structural families: LAM from fast-growing, non-pathogenic species, such as M. smegmatis, have uncapped ends (AraLAM) or inositol phosphate caps (phosphatidyl-myo-inositol capped LAM, or PILAM) whereas LAM from slow-growing mycobacteria (Mtb, M. leprae, M. avium, and M. kansasii) is modified with one to three α (1→2)-linked mannopyranose (Manp) units (ManLAM). Mtb ManLAM can contain an additional cap modification, 5-deoxy-5-methylthio-xylofuranose (MTX), attached to the terminal Manp [13][14][15].…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%
“…According to the capping motifs, LAM can be classified into three structural families: LAM from fast-growing, non-pathogenic species, such as M. smegmatis, have uncapped ends (AraLAM) or inositol phosphate caps (phosphatidyl-myo-inositol capped LAM, or PILAM) whereas LAM from slow-growing mycobacteria (Mtb, M. leprae, M. avium, and M. kansasii) is modified with one to three α (1→2)-linked mannopyranose (Manp) units (ManLAM). Mtb ManLAM can contain an additional cap modification, 5-deoxy-5-methylthio-xylofuranose (MTX), attached to the terminal Manp [13][14][15].…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%
“…In our previous study by Paris et al 6 , we demonstrated that it is possible to detect urinary LAM in HIV negative TB patients using an experimental workflow which included a pre-analytical concentration step. Other investigators confirmed these findings 7,8,17,18,25 . Recent reports of LAM immunoassays employing high affinity purified antibodies indicate that acceptable analytical sensitivity required for HIV negative TB positive patients can be achieved without the use of a pre-analytical concentration step.…”
Section: Discussionmentioning
confidence: 60%
“…Median urinary LAM concentration in TB negative patients was 0.016 ng/mL (IQR = 0.07), 0.03 ng/ mL (IQR = 0.06), and 0.03 ng/mL (IQR = 0.05) for MoAb1, CS35 and A194, respectively. 8 , Amin et al 17 , and De et al 18 . (B) Calibration curve of anti-LAM antibodies.…”
Section: Resultsmentioning
confidence: 97%
“…Generally the disease progresses in five stages (Rhoades, Frank, & Orme, 1997), which are based on the extent of granulomatous involvement, the cell types present, the degree of lymphocyte organization, and the presence of destructive sequelae such as airway epithelium erosion and airway debris. Many of these parameters can be used to give an overall group ranking or lesion score based on histopathological assessments by a qualified veterinary pathologist (Basaraba, 2008;De et al, 2020).…”
Section: Of 52mentioning
confidence: 99%
“…The one notable disadvantage of the majority of mouse models is that the pulmonary and extra-pulmonary pathology following aerosol challenge lacks important morphologic features that are commonly seen in humans with untreated tuberculosis. To model these aspects, the guinea pig low-dose and the C3HeB/FeJ mouse aerosol infection models have been further developed in recent years, since they share many of these clinical features with the human disease (Basaraba, 2008;McMurray, 2003, De et al, 2020Shang, Harton et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%